Home-stay: Assessment in Lwang Ghalel - Thapaliya, Mandira; Rai, Ganga Sagar; Shrestha, Abhash; Parajuli, Binaya; Pande, Ojeswee (Nepal Tourism and Development Review, 2013)
Home-stay tourism is a community-based programme introduced by the Government of Nepal, where tourists can have interaction and direct experience of the day-to-day life of the community. The concept of home-stay addresses the theme of eco-tourism in Nepal. The programme’s preliminary positive impact on women, local economy, environment, children and the community shows the effectiveness of the home-stay approach. This approach preserves the rural lifestyle, culture and identity. A growing number of locals are operating the home-stay programme, offering tourists a window into their local culture in areas without hotels. This paper briefly outlines the findings of a field research on the different aspects of home-stay tourism in Wards 2 and 3 of Lwang Ghalel Village Development Committee in Kaski district1. The study includes aspects which both help promote as well as adversely affect the operation of home-stay in the study area. DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7382 Nepal Tourism and Development Review Vol.2(1) 2012 105-140